Applications of Next-Generation Sequencing Technologies and Computational Tools in Molecular Evolution and Aquatic Animals Conservation Studies: A Short Review. (December 2019) - Tan, Min Pau; Wong, Li Lian; Razali, Siti Aisyah; Afiqah-Aleng, Nor; Mohd Nor, Siti Azizah; Sung, Yeong Yik; Van de Peer, Yves; Sorgeloos, Patrick; Danish-Daniel, Muhd
Aquatic ecosystems that form major biodiversity hotspots are critically threatened due to environmental and anthropogenic stressors. We believe that, in this genomic era, computational methods can be applied to promote aquatic biodiversity conservation by addressing questions related to the evolutionary history of aquatic organisms at the molecular level. However, huge amounts of genomics data generated can only be discerned through the use of bioinformatics. Here, we examine the applications of next-generation sequencing technologies and bioinformatics tools to study the molecular evolution of aquatic animals and discuss the current challenges and future perspectives of using bioinformatics toward aquatic animal conservation efforts.